In Silico Exploration of Podophyllum Hexandrum-Derived Phytocompounds as Potential Therapeutics Against Small Cell Lung Cancer (SCLC): A Molecular Docking Approach - Akanksha Kriti (International Journal of Molecular Biotechnological Research, 2025)
Small Cell Lung Cancer (SCLC) is a fast-growing and aggressive type of lung cancer that spreads quickly strongly associated with smoking. It is characterized by symptoms, such as persistent cough, breathing difficulties, or hoarseness, though it can sometimes be asymptomatic which makes early detection challenging. The tumor suppressor gene TP53 is critical in regulating the cell cycle and preventing uncontrolled cell division. Mutations in TP53 result in the loss of its tumor-suppressing function, facilitating the development and progression of cancers like SCLC. Podophyllum hexandrum (PH), a medicinal plant known for its anticancer properties, has demonstrated significant therapeutic potential in inhibiting tumor growth and progression. PubChem is a primary resource for obtaining information and molecular structures of the phytocompounds. Various other tools were utilized to perform pharmacological assessments, particularly analyzing the ADME properties of these compounds. ProTox-II is a tool employed for toxicity prediction, ensuring the safety and efficacy of the identified compounds. This study explores the ability of phytocompounds derived from PH to target TP53 mutations in SCLC through molecular docking analysis. Molecular docking provides a computational approach to identify potential drug candidates by estimating how strongly they interact with target proteins. Using PyRx and BIOVIA, molecular. docking revealed that specific phytocompounds from PH demonstrated strong binding affinities as antagonists against mutated TP53, a key factor in SCLC progression. These findings highlight the significant potential for developing effective drug candidates to target SCLC, offering a promising path for therapeutic development. This study will focus on computational drug discovery, facilitating faster drug candidate identification, cost and time reduction, and optimization prior to experimental testing.
Keywords: Small cell lung cancer; TP53 gene; in silico analysis; molecular docking; podophyllum hexandrum